The development of b2b e-marketplace for dropshipping / Mohammad Aiman Ismail and Nor Azila Awang Abu Bakar - Ismail, Mohammad Aiman; Awang Abu Bakar, Nor Azila (Universiti Teknologi MARA, Perak, 2018)
E-marketplace is an online market platform where business parties can register as buyers or sellers to conduct business to business transactions over the Internet. Dropshipment refers to the delivery of goods from a manufacturer to a buyer without passing through the retailer or dropship agents. The retailer or dropship agents are the ones who contribute in the generating, processing and marketing part of the sale. However, the major problems that can be foreseen in dropshipping are in the scope of interaction and the transaction process. The business parties might find it difficult to manage both personal and business interaction in a single application. In addition, the business parties would have to jump into several different websites to conduct a single transaction. Hence, a B2B e-marketplace to assist dropship agents and their suppliers for conducting business is proposed. The e-marketplace prototype (A&S.com) was developed by adapting the Waterfall model and was evaluated in terms of functionality and usability by three (3) expert users and thirty (30) other respondents.